Preparation of future social teachers to work with a patronate family - Volodymyr Kostiv; Ludmyla Vavryshchuk (Vasyl Stefanyk Precarpathian National University, 2018)
The article sets out to establish practicability of special training of future social teachers to work with a patronate family as one of the family types with disturbed structure. It indicates possibilities of establishment of a patronate family institute as an alternative form of family upbringing of orphaned children and children deprived of parental care. It outlines constituents of social teacher readiness for organization social and pedagogical activities with a patronate  family: professional and humanistic orientation, intellectual and cognitive component represented by professional and pedagogical knowledge and skills,  action-oriented practical component which is characterized by availability of personal experience of student's interaction with the patronate families, with other forms of family establishment of orphaned children and children deprived of parental care, with parents, adopted children, professionals providing social support of these families, representatives of government authorities which promote family forms of upbringing. Key words: orphaned children and children deprived of parental care, patronate family, future social teachers, constituents of social teacher readiness for organization social and pedagogical activities with a patronate family.